Clinical Presentation of Infertility in Mkar-Gboko, North-Central Nigeria - Karshima, Jonathan Abina; Pam, Victor Chuwang; Shambe, Iornum Hembe; Anyaka, Charles Ujunwa; Reich, Michael Ira (International Journal of Medical and Health Sciences Research, 2016)
Infertility is a worldwide health concern with dissimilarities in mode of presentation among couples. It is the commonest reason for gynaecological consultation in central Nigeria. Therefore there is need to appraise the clinical presentation of infertility and describe the manner of presentation by women in the region. Aim: To identify the mode of presentation and pattern of presenting complaints by women with infertility at a rural gynaecological outreach clinic. Method: A descriptive retrospective study at NKST Hospital Mkar-Gboko, north-central, Nigeria. Clinic records of patients who attended the outreach gynaecological clinic over eight years (1st January 2005 to 31st July 2013) were analysed using descriptive statistics with Excel 2010. Results: Of the 1,926 women studied, 1030 (53.5%) complained of inability to conceive, and 941 (92.0%) folders met inclusion criteria. Women with primary and secondary infertility were 264(28.1%) and 677(71.9%) respectively. The mean (±SD) age, parity and duration of infertility of the women were 31.5±5.9 year, 0.8±1.2, and 7 ±5 years respectively. The predominant complaints were inability to conceive, lower abdominal pain, abnormal menstruation, lower abdominal swelling and vaginal discharge. Majority of the women (55.0%) skipped inability to conceive as their chief complaint. In past surgical history, 194 (20.6%) of the women had 234 abdominal surgeries. On physical examination 538 (57.2%) of the women had no remarkable findings. Abdominal scar (n=194, 47.0%), enlargement of the uterus (n=166, 40.0%), vaginal discharge (n=42, 10.0%) were common findings. Conclusion: Non acute lower abdominal pain is a common mode of presentation of infertility in this population. The duration of marriage/age of last childbirth against the number of living children and contraceptive usage can be a clue to the woman’s desire.